361 The relationship between intracranial MRI abnormalities and post-concussive symptoms in ED patients with a normal CT: as demonstrated on the Rivermead Post Concussion Symptom Questionnaire (RPQ). Issue 12 (23rd November 2020) - Whitehouse, Daniel; Richter, Sophie; Winzeck, Stefan; Kornaropoulos, Evgenios N; Das, Tilak; Vyvere, Thijs Vande; Verheyden, Jan; Williams, Guy B; Correia, Marta M; Menon, David K; Newcombe, Virginia FJ; ,
Abstract : Aims/Objectives/Background: Mild traumatic brain injury (TBI) is common presentation to the ED. Mild, however, is a misnomer with 10–40% of patients suffering from post-concussion symptoms for months to years following injury. 1 2 Patients often re-present to primary care or ED with these symptoms, and the role of repeat imaging in this cohort remains uncertain. Aims: assess TBI patients discharged from the ED with no acute intracranial findings on CT head scan, who subsequently had a research-driven MRI and documented 3-month RPQ, to determine the association between ongoing post-concussion symptoms and MRI pathology. Methods/Design: 91 patients in the CENTER-TBI dataset met the inclusion criteria. 3 Mann-Whitney U test used to compare 3-month RPQ and MRI findings. Numbers and percentages of patients with RPQ >35 and >19 presented owing to a score of 35 predicting moderate to severe activity limitation, 4 and 19 representing mean RPQ in patients with diagnosed post-concussion syndrome (PCS). 2 Results/Conclusions: 15/91 CT-ve (16.5%) patients had abnormalities on acute MRI (2 intraparenchymal haemorrhages, 13 Diffuse Axonal Injury (DAI)). No significant difference between median 3 month RPQ between MRI -ve (2.00 [IQR 0.00 – 14.00] and MRI +ve (0.00 [IQR 0.00 – 8.50]) patients (p=0.51, Mann-Whitney U test). Of patients with a RPQ >35, only 1/8 (12.5%) had a +ve MRI. Of patients with a RPQ >19 2/14 (14.3%) had +ve MRI, both DAI. No difference was found between RPQ scores of MRI positive and negative patients, suggesting no significant relationship between ongoing symptomology following mild TBI and gross MRI findings in patients with a negative acute CT. This study is limited by a small number of patients with positive neuroimaging and a lack of quantitative MRI data. Further prospective research is required to assessing a larger patient cohort and more sensitive imaging modalities to examine the utility of repeat neuroimaging in patients with ongoing concussive symptoms. References: Polinder S, Cnossen MC, Real RGL, et al . A multidimensional approach to post-concussion symptoms in mild traumatic brain injury. Front. Neurol 2018;9 :1113. doi:10.3389/fneur.2018.01113 Ingebrigtsen T, Waterloo K, Marup-Jensen S, et al . Quantification of post-concussion symptoms 3 months after minor head injury in 100 consecutive patients. J Neurol 1998;245 :609–12. doi:10.1007/s004150050254 Maas AIR, Menon DK, Steyerberg EW, et al . Collaborative European neurotrauma effectiveness research in traumatic brain injury (CENTER-TBI): A prospective longitudinal observational study. Neurosurgery 2015;76 :67–80. doi:10.1227/NEU.0000000000000575 De Guise E, Bélanger S, Tinawi S, et al . Usefulness of the rivermead postconcussion symptoms questionnaire and the trail-making test for outcome prediction in patients with mild traumatic brain injury. Appl Neuropsychol 2016;23 :213–22. doi:10.1080/23279095.2015.1038747